Primary Giant Cell Tumor of the Breast With Pulmonary Metastasis: A Case Report and Review of the Literature - Zhang, Wenxiang; Kong, Xiangyi; Qi, Yihang; Wang, Xiangyu; Liu, Qiang; Fang, Yi; Song, Yan; Wang, Jing (Frontiers in Oncology, 2021)
Giant cell tumor of soft tissue (GCT-ST) is an extremely rare tumor that is similar in morphology and immunohistochemistry to giant cell tumor of the bone. Almost 80% of these tumors occur in the upper and lower extremities, and the breast is a very rare location. Here, we report a case of a 65-year-old female patient with a small mobile palpable lump in the left breast. Although the left breast tumor was considered malignant on preoperative imaging, no evidence of malignant tumor was found by ultrasound-guided core needle biopsy (CNB). Subsequently, the left breast tumor was confirmed as a malignant tumor by intraoperative rapid pathological examination. The initial treatment of the tumor was wide local excision and sentinel lymph node biopsy, and it was confirmed to be GCT-ST by histopathology and immunohistochemistry. Despite surgical treatment achieving clear surgical margins, the patient experienced lung metastases within a year of her initial treatment. Fortunately, the patient underwent surgical treatment of lung metastases, and at the last follow-up, the patient was still alive. This is the first case of a primary soft tissue tumor of the breast that has undergone surgical intervention after lung metastasis. This case report highlights the complexity of the clinical diagnosis and treatment of GCT-ST arising from the breast. Surgery may be another good treatment when the patient develops lung metastases.